Ursodeoxycholic acid therapy in cystic fibrosis liver disease - a retrospective long-term follow-up case-control study - Kappler, M.; Espach, C.; Schweiger-Kabesch, A.; Lang, T.; Hartl, D.; Hector, A.; Glasmacher, C.; Griese, M. (Alimentary pharmacology & therapeutics, 2012)
Summary Background The prevention and treatment of liver disease associated with cystic fibrosis remain a significant unresolved problem. Aim To assess the long‐term effects of continuous ursodeoxycholic acid (UDCA) therapy in cystic fibrosis patients with constantly elevated serum liver enzymes. Methods The primary endpoint was the incidence of overt liver disease. Between 1989 and 2005, UDCA treatment was started in 98 subjects from a cohort of 382 cystic fibrosis patients. These subjects were compared with a historic control group of 352 subjects who attended our centre between 1975 and 1989 before UDCA became standard treatment. For the long‐term comparison of liver function and lung function tests, a group of 98 matched contemporary cystic fibrosis patients were compared with the 98 subjects treated with UDCA. Results Overt liver disease developed in only one of the 382 patients who was treated with UDCA for increased serum liver enzymes compared with nine patients in the historic control group (P < 0.05). Serum liver enzyme levels declined in most patients receiving UDCA treatment during the 17‐year follow‐up (87/98, P < 0.05). No difference was seen in lung function between subjects with cystic fibrosis‐related liver disease and the matched controls. Conclusions Regular and systematic screening for liver involvement enables early introduction of UDCA therapy in affected cystic fibrosis patients, reduces the development of severe liver disease and leads to a significant and persistent improvement in serum liver tests, without impairing long‐term pulmonary outcome.